Efficacité de produits de nettoyage et disifection contre les bactéries dans une entreprise fromagrie - Bougueroudjs, Samira; Bendahman, Mokhtaria (My University, 2020)
This study was carried out with the aim of monitoring the cleaning and disinfection system adopted by the Sidi Saada dairy at the level of the camembert production unit. To this end, microbiological analyzes are carried out on the waters of final rinse, the microbiological analyzes consist in the search for FMTA and total and faecal coliforms. The hygiene of personnel and the materials of the Camembert production line were checked. These analyzes showed effective CIP cleaning with a virtual absence of microorganisms in the final rinsing water and compliance with the recommended sodium and acid concentrations. The analyzes carried out on the equipment showed contamination by total coliforms, especially at the level of the mold blocks. For personal and environmental hygiene, analyzes have shown that progress needs to be made at this level, since we observed the presence of total coliforms even after cleaning the hands. For the environment, a strong development of mucor and yeast. The analyzes carried out on the finished product confirm its good microbiological quality.
Keywords: Hygiene; NEP; Cleaning; Disinfection.